Vanishing vasculitis: a case of acute necrotic skin findings without pathologic features of vasculitis from adulterated cocaine - Adnan Asif Parvez Ghias; Patrick Brine (Journal of Community Hospital Internal Medicine Perspectives, 2017)
While the usage of illicit drugs in itself carries significant health risks and associated toxicities, drugs that are adulterated to give them volume, alter their psychogenic properties, and make them cheaper to produce are to be considered even more dangerous. Cocaine is one of them, and it is now most commonly being adulterated with levamisole. We report a case of a 37-year-old female with the chief complaint of painful skin lesions and wounds on both of her upper and lower extremities for three weeks duration. She was tested positive for cocaine and had classical purpuric, ecchymotic, and necrotic patches on both ears, which are pathognomonic. She also had multiple wounds in extremities. The cocaine–levamisole related syndrome comprises a set of immunological abnormalities, out of which, ANCA positivity is the most important one. Our patient was ANCA positive. Regarding pathological findings in cocaine adulterated with levamisole syndrome, this can range from the classic finding of leukocytoclastic vasculitis of small vessels to occlusive vascular disease without true vasculitis. Our case’s biopsy showed no vasculitis, and this is why it is important to highlight that cocaine can also cause a pseudo-vasculitic picture. The other possibility that we entertained was that of pyoderma gangrenosum as the skin finding in levamisole-contaminated cocaine, and the lesion was consistent in appearance. Recently, there have been a few case reports of pyoderma gangrenosum from adulterated cocaine with levamisole, where skin findings were consistent with pyoderma gangrenosum; however, serological findings rather favored levamisole vasculopathy or vasculitis. Therefore, we should familiarize ourselves with the multitude of pathological and skin findings that adulterated cocaine can cause and, finally, make ourselves aware that the classical pathological finding of vasculitis in such cases is not always seen.